2011
DOI: 10.4061/2011/352538
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Machinery of a Key Enzyme in Amino Acid Biosynthesis

Abstract: The aspartate pathway of amino acid biosynthesis is essential for all microbial life but is absent in mammals. Characterizing the enzyme-catalyzed reactions in this pathway can identify new protein targets for the development of antibiotics with unique modes of action. The enzyme aspartate β-semialdehyde dehydrogenase (ASADH) catalyzes an early branch point reaction in the aspartate pathway. Kinetic, mutagenic, and structural studies of ASADH from various microbial species have been used to elucidate mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…1). The presented structural data support this proposal and revealed a remarkable relationship between the active sites of MCR and ASD that allows a direct application of the wealth of structural and mechanistic data available for ASD (13). This high degree of conservation, despite substantial differences of the substrates used, becomes comprehensible when considering similarities between the aspartate and malonate/ succinate and the CoA and NADP ϩ structures as well as between the catalyzed reactions.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…1). The presented structural data support this proposal and revealed a remarkable relationship between the active sites of MCR and ASD that allows a direct application of the wealth of structural and mechanistic data available for ASD (13). This high degree of conservation, despite substantial differences of the substrates used, becomes comprehensible when considering similarities between the aspartate and malonate/ succinate and the CoA and NADP ϩ structures as well as between the catalyzed reactions.…”
supporting
confidence: 73%
“…glyceraldehyde-3-phosphate dehydrogenase; however, the physiological role is not known (11,12). An x-ray structure was so far not reported for MCR but for homologous enzymes, with the most related being the well characterized aspartate-␤-semialdehyde dehydrogenase (ASD) (13). However, MCR catalyzes a different reaction, which might implicate significant differences in the active site architecture and the enzymatic mechanism.…”
mentioning
confidence: 99%
“…Although this process is essential in microorganisms, it is absent in mammals. Thus, this could possibly aid in the development of antibiotics targeting the proteins of the aspartate family amino acid metabolic processes (38,39). The KEGG analysis indicated that the overlapping protein hits of Bac7 and PR-39 were overrepresented in fructose and mannose metabolism and in terpenoid backbone biosynthesis.…”
Section: Validation Of Synergistic Effects Of Bac7 and Lfcinb As Wellmentioning
confidence: 99%
“…1). 6 It catalyzes the conversion of L-homoserine to O-acetyl-L-homoserine (OAHS) by transfer of an acetyl group from Acetyl-CoA to the γ -hydroxyl of homoserine. This transfer uses a doubledisplacement mechanism facilitated by a Ser-His-Asp catalytic triad.…”
Section: Introductionmentioning
confidence: 99%